Post Varicella-Zoster virus transverse myelitis: Diagnostic and therapeutic challenges – A case report and literature review - Mohammad Mehdi Shadravan; Farnoosh Farshchian; Alireza Rajaei; Ilad Alavi Darazam; Reza Naseri; Faezeh Maghsudloo (IDCases)
Introduction: Acute transverse myelitis (ATM) is a rare inflammatory disorder that affects the spinal cord, leading to sudden weakness, sensory deficits, and bowel/bladder dysfunction. Also rare, this condition can be caused by infections such as the Varicella-zoster virus (VZV) or can occur as a complication of systemic lupus erythematosus (SLE). It has been reported to be more prevalent in SLE patients compared to VZV infections. We present a case of a patient with a history of SLE and evidence of vesicular rash from VZV infection. Case report: A 61-year-old female presented with progressive weakness in her lower limbs. Two weeks before, she had developed a vesicular rash due to a VZV infection in the T6-T9 dermatomes, which was followed by paraparesis, sensory loss, and urinary retention. She also had a history of SLE. During the physical examination, muscle strength and sensation were decreased in the lower limbs. MRI revealed central myelopathy from T6 to T10. In laboratory tests, VZV PCR was positive, and Aquaporin-4 was also negative. The patient was treated with IV corticosteroid pulse and ganciclovir, followed by plasma exchange. resulted in partial recovery. Conclusions: This case highlights VZV-induced TM (VZV-TM) in an immunocompromised patient with underlying SLE. Despite overlapping etiologies, a thorough clinical, radiologic, and laboratory evaluation, including a positive CSF VZV PCR and the absence of a SLE flare, supported VZV-TM as the final diagnosis. Prompt antiviral therapy and escalation to plasma exchange led to substantial neurological recovery.